Electroencephalography in Intensive Care and Electroencephalography in Diagnosis of Brain Death: Clinical Case Reports - (:unkn) unknown (TURKIYE KLINIKLERI, 2019)
Continous EEG monitoring in intensive care units is a unique method for evaluation of coma. Because EEG demonstrates a high sensitivity to alterations of cerebral function, it is very useful for diagnosis, follow-up and evaluation of therapy of various coma etiologies. EEG is especially a convenient method for the follow-up of hypoxic-ischemic destruction, seizures and effects of drugs.
Keywords: Intensive care unit; continuous Electroencephalography monitoring; coma; encephalopathy; nonconvulsive seizures; EEG